A cor da dança: representatividade negra no ballet clássico na cidade de Belém do Pará - ANJOS, Ariany Vitória Coelho dos (2023)
The present work seeks to understand the importance of black representation in classical ballet from my experiences as a dancer. Bringing reports on field research, I seek to raise reflections and questions about the structural racism present in this scenic dance, and I highlight the need for more black dancers occupying places of notability in schools and dance companies in Belém do Pará. In order to investigate the prejudice within ballet, I talk to authors such as HOMANS (2012) and SAMARINO (2021) to bring the origin of this dance in European lands, In addition to SILVÉRIO (2020) and SILVA (2021) to support the dialogue on the exclusion of black girls in main roles in dance. The methodology used was the autobiographical research according to ALVES (2015), understanding as a self-investigation of my personal and professional life trajectory, as a black dancer within a dance with European origin. Finally, I conclude that ballet should be accessible to everyone who dreams of it and have black references in this environment, little by little, it breaks a standard imposed by racism.